Optimality conditions for fractional variational problems with dependence on a combined Caputo derivative of variable order - Tavares, D.
We establish necessary optimality conditions for variational problems with a Lagrangian depending on a combined Caputo derivative of variable fractional order. The endpoint of the integral is free, and thus transversality conditions are proved. Several particular cases are considered illustrating the new results.